Working with parents in therapy : a mentalization-based approach - Malberg, Norka T.; Jurist, Elliot L., 1953-; Bate, Jordan (American Psychological Association, 2023)
"This book presents parenthood as a developmental process that can be supported by a mentalization-based model of intervention"--